Wonder in early modern Ottoman society: A case study in the history of emotions - Ben-Ami, Ido (History compass, 2019)
The questions what an emotion is and how it is generated can be answered in multiple ways. Usually, the answer depends on the disciplinary perspective. As was recently noted by several dominant historians who deal with the history of emotions, although the biological and psychological elements of a certain feeling should not be ignored, within historical research, a focus on social and cultural aspects of emotion generation seems to be more convincing. In this article, I address this issue in the context of Ottoman studies from the perspective of Barbara H. Rosenwein's notion of "emotional communities." I consider early modern Ottoman elite society of Istanbul to be such a community and demonstrate how several powerful individuals from this large social group relied on a medieval Islamic theory about cosmographic "wonder" and encouraged its members to embrace this emotion into their social and cultural milieus.